CANVA SEBAGAI MEDIA INOVATIF DALAM PEMBELAJARAN SHOROF - Siti Kholifah; Rizka Sari (LP2M IAIN Sultan Amai Gorontalo, 2025)
The digital transformation in education has fostered the development of interactive learning media tailored to 21st-century student needs. One subject that requires innovative approaches is Shorof in Arabic, often seen as abstract and difficult by students in elementary Islamic schools. This study aims to evaluate the effectiveness of Canva-based educational games in improving Shorof learning outcomes at MIN 3 Rokan Hulu. Using a quantitative quasi-experimental design, the study involved two groups of fifth-grade students: one experimental (Canva) and one control (traditional methods). Data were collected through pre-tests, post-tests, observations, and questionnaires. Results showed a significant improvement in the experimental group’s post-test scores, with a 20.25-point increase compared to 8.75 in the control group (t-test p = 0.003 < 0.05). Observations and surveys also indicated greater engagement and motivation. In conclusion, Canva-based game media significantly enhance Shorof learning, aligning well with the Merdeka Curriculum's digital learning goals.